Frost and drought: Effects of extreme weather events on stem carbon dynamics in a Mediterranean beech forest. (24th August 2020) - D'Andrea, Ettore; Rezaie, Negar; Prislan, Peter; Gričar, Jozica; Collalti, Alessio; Muhr, Jan; Matteucci, Giorgio
Abstract: The effects of short‐term extreme events on tree functioning and physiology are still rather elusive. European beech is one of the most sensitive species to late frost and water shortage. We investigated the intra‐annual C dynamics in stems under such conditions. Wood formation and stem CO2 efflux were monitored in a Mediterranean beech forest for 3 years (2015–2017), including a late frost (2016) and a summer drought (2017). The late frost reduced radial growth and, consequently, the amount of carbon fixed in the stem biomass by 80%. Stem carbon dioxide efflux in 2016 was reduced by 25%, which can be attributed to the reduction of effluxes due to growth respiration. Counter to our expectations, we found no effects of the 2017 summer drought on radial growth and stem carbon efflux. The studied extreme weather events had various effects on tree growth. Even though late spring frost had a strong impact on beech radial growth in the current year, trees fully recovered in the following growing season, indicating high resilience of beech to this stressful event. Abstract : Late frost affected C stem dynamics of Mediterranean beech trees more than summer drought. Even though frost had a devastating impact on the growth and consequently on stem C efflux, trees fully recovered in the following growing season, indicating high resilience to this stressful event.